Aberrant expression of PYGB as a potential therapeutic target and its associations with immune cell infiltration in lung cancer - Sun, Kai; Xu, De-chang; Qin, Xia; Xie, Fang-fang (Frontiers in Immunology, 2025)
BackgroundBrain glycogen phosphorylase (PYGB) facilitates the breakdown of glycogen, thereby supplying energy to tumor cells. While PYGB expression has been documented in various tumor types, its specific function in lung cancer (LC) remains to be elucidated. This study aims to explore the potential involvement of PYGB in the initiation and progression of LC.Methods and resultsWe systematically analyzed PYGB in LC using data from the Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) Cancer database, employing R and various online analytical tools. Elevated PYGB expression was observed in LC and was associated with poor clinical outcomes. In vitro experiments, immunohistochemistry (IHC) confirmed the aberrantly high expression of PYGB in LC. The application of PYGB-siRNA significantly inhibited the proliferation, migration, and invasion of LC cells. Further analysis demonstrated correlations between PYGB expression and immune infiltration, immune checkpoint expression, tumor mutation burden, and microsatellite instability in LC.ConclusionsThis study unveils that elevated PYGB expression in LC is significantly correlated with poor prognosis, potentially attributable to PYGB’s facilitation of LC cell proliferation, migration, and metastasis, as well as its significant association with the immune microenvironment.